SEISMOTECTONIC MODELLING OF THE SUNDA ARC WITH COULOMB STRESS ANALYSIS - (NIM 12404005); Pembimbing: Wahyu Triyoso, Ph.D., ULANDARI
Studies of seismotectonic in Sumatra are needed to obtain seismotectonic behavior. Seismotectonic study can be done by observation of displacement vectors, strain, and also stress occurance. This study is uses Sumatra Fault Data and Sumatra Subduction Data from Sieh and Natawidjaja. We will analyze seismotectonics behavior for 100 and 500 years before release energy until after release energy. Especially, in this study we will compare Nias seismotectonics after Aceh shock on December 2004. By using Coulomb failure stress change Analysis aftershock, we will know about potential failure nearby Sumatra Fault Zone in the future.